Binding to large enzyme pockets: small-molecule inhibitors of trypanothione reductase - Persch, Elke; Bryson, Steve; Todoroff, Nickolay K.; Eberle, Christian; Thelemann, Jonas; Dirdjaja, Natalie; Kaiser, Marcel; Weber, Maria; Derbani, Hassan; Brun, Reto; Schneider, Gisbert; Pai, Emil F.; et al. (ChemMedChem, 2014)
Abstract The causative agents of the parasitic disease human African trypanosomiasis belong to the family of trypanosomatids. These parasitic protozoa exhibit a unique thiol redox metabolism that is based on the flavoenzyme trypanothione reductase (TR). TR was identified as a potential drug target and features a large active site that allows a multitude of possible ligand orientations, which renders rational structure-based inhibitor design highly challenging. Herein we describe the synthesis, binding properties, and kinetic analysis of a new series of small-molecule inhibitors of TR. The conjunction of biological activities, mutation studies, and virtual ligand docking simulations led to the prediction of a binding mode that was confirmed by crystal structure analysis. The crystal structures revealed that the ligands bind to the hydrophobic wall of the so-called ?mepacrine binding site?. The binding conformation and potency of the inhibitors varied for TR from Trypanosoma brucei and T.?cruzi.